PENYULUHAN KESEHATAN PENDAMPINGAN PRAKTEK PEMASANGAN TENSOCREPE SENDI (Poltekkes Kemenkes Bandung, 2023)
Background: Sprains (dislocations) can occur suddenly without us realizing it, this can happen at home or outside the home while working, exercising, playing, and so on. It needs proper handling because tensocrepe is a simple tool. In First Aid for Accidents (P3K) which is required especially for assistance to victims, of sprains. Objectives: Students understand sprains and can practice and provide tensocrepe on sprained joints. So that the injured joint does not shift to avoid the spread of injury to the muscle tissue around the injured joint. Activity Results: Counseling was attended by class IV students. SDN.07 Rejang Lebong 10 female and 11 male students, 98 % of the students could answer the quiz questions directly about sprains and were able to practice and provide tensocrepe on sprained joints.Follow-up Plan: Tensocrepe installation training activities will occur in other classes. Discussion: Tensocrepe installation is first aid for sprained joints, by maintaining the position of the injured joint using tensocrepe installation, can maintain a stable position, and the injury does not spread. Conclusion: 98 % of students can answer quiz questions directly about sprains and can practice and provide tensocrepe on sprained joints. so that the injured joint does not shift and to avoid spreading injury to the muscle tissue around the injured joint. Suggestion: Students who have been given tensocrepe installation training should socialize it with friends and family.